(untitled) (Praxis Educativa, 2022)
The article aims to understand the tensions in the intercultural educational relationships between a mentor teacher, traditional educator and students in La Araucania. The theoretical perspective that sustains the discussion is the schooling based on the Western Eurocentric school curriculum and family education in Mapuche context, for which the students are subjected to a double immersion: school and family education. The methodology used is educational research, based on a school ethnography and content analysis. The main results show the reproductions of institutionalized racism in school education, an epistemological difference in relation to the contents desired to transmit in the implementation of intercultural education, and a systematic invisibility, both of knowledge and of traditional students and educators in schooling processes.